Agricultural Innovation in the Volta River Basin: An Analysis of Changes in Knowledge, Skills and Livelihoods brought about by the Volta Basin Development Challenge - Lasiter, Kalie; Tarrant, Anna (CGIAR Challenge Program on Water and Food, 2013)
Main message Farmers in Volta Basin Development Challenge project sites are generally not developing brand new practices on their own. Information about new technologies is slowly spreading from projects to the wider community, but adoption of these technologies could be strengthened by creating an enabling environment. This would mean taking into account the five determinants of adoption identified here and programming accordingly.